Effect of Fermented used rice as a functional feed on biochemical and haematological parameters, microbial population, internal organ weight and performance of broilers - Yudiarti, T.; Widiastuti, E.; Wahyuni, H. I.; Pramono, Y. B. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
The study aimed to evaluate effect of the used rice fermented using Chrysonillia crassa as a functional feed on biochemical and haematological parameters, microbial populations, internal organ weight and performance of broilers. The study used one hundred and fifty unsexed one-day-old chicks with average body weight of 48.30 ± 4.13g. At day 1 to 7, the chicks were given commercial feed.  On day 8 onward, the chickens were randomized distributed to one of three experimental diets of 50 chicks each. The chicks were given formulated diet containing fermented used rice based-functional feed (FF). Drinking water was provided ad libitum. The study used completely randomized design with three experimental diets : T0 (diet without FF), T1 (diet contained 5% FF), and T2 (diet contained 10% FF). The chicken fed the used rice fermented increased in cholesterol, high density lipoprotein status, mean corpuscular haemoglobin concentration, lactic acid bacteria, heart weight. and decreased in mean corpuscular volume, E.coli, jejunum weight, but no affect on body weight gain, feed convertion ratio and feed comsumption. In conclusion that the fermented used rice improved the physiological conditions,intestinal bacterial population and had no detrimental effect on performance of broiler.